ANALISIS FINANSIAL HUTAN RAKYAT DI KECAMATAN JABIREN RAYA KABUPATEN PULANG PISAU KALIMANTAN TENGAH : Fierta Tirtajaya, I Nyoman Surasana, Nursiah - Admin JHT (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2016)
ABSTRACK One of some methods to conserve the peat forest species is increasing the local peoples income. In order that the research regarding financial and economic analyzis of forest community at the peat forest is significant needed. The aim of this research was to know the benefit of forest community project that be developed at the Jabiren Raya, Pulang Pisau District, Central Kalimantan Province. The research was done using interview agree with list of questioner and literature study. Research result showed that cultivation of Dyre lowii and Hevea brasiliensis are profitable with NPV and BCR namely IDR 67.5 mill and 1.36, 31.4 mill and 1.19, and 5.5 mill and 1.04 per ha at the bank rate of 13%, 15%, and 17% respectively. Profitable of IRR namely 18% bigger than social bank rate. Keynotes: Dyre lowii, Financial, forest community, Hevea brasiliensis